Understanding occupational engagement for individuals with bariatric needs: The perspectives of Australian Occupational Therapists - Ellison, N.; Keesing, Sharon; Harris, Courtenay (2020)
© 2020 Occupational Therapy Australia Introduction: Over the last 20 years, the number of individuals affected by obesity in Australia has increased by 56%. The impact of excessive weight gain results in a wide range of physical, psychological and social difficulties, with resultant changes to occupational performance and engagement. For some people within this population, a further consequence of this increasing weight gain contributes to additional difficulties, with the individual being considered to be “bariatric”. For these people, resultant changes include decreased capacity to engage in self-care activities, leisure occupations and productive roles, creating significant difficulties in undertaking important life roles. This phenomenological study aimed to understand the occupational engagement of individuals with bariatric needs, and to identify potential opportunities to support the engagement and participation of these individuals from the perspectives of Australian occupational therapists. Methods: Qualitative data were collected from 11 semi-structured interviews with occupational therapists from a variety of practice settings. Results: Thematic analysis identified four central themes (a) Occupational engagement was significantly impacted by a lack of suitable resources and availability of daily living equipment; (b) Health and well-being were impacted by a disruption in meaningful occupational engagement; (c) Occupational roles were limited due to poor occupational identity and perceptions of not belonging within the community; (d) Occupational therapists do have a varied role when working with individuals with bariatric needs. Conclusion: Occupational therapists engaged in this study indicated that people with bariatric needs were significantly impacted by many complex issues as a result of their health condition, often contributing to poor health and decreased well-being. Occupational therapists are well-placed to engage with individuals with bariatric needs across many care contexts and must take up potential opportunities to provide services targeted towards the increased engagement and participation of these individuals, with resultant improvements to health and well-being.